The effect of magnification and contrast on reading performance in different types of simulated low vision - Michael Christen; Mathias Abegg (Bern Open Publishing, 2017)
Low vision therapy, such as magnifiers or contrast enhancement, is widely used. Scientific evidence proving its efficacy is scarce however. The objective of this study was to investigate whether the benefits of magnification and contrast enhancement depended on the origin of low vision. For this purpose we measured reading speed with artificially induced low vision in 12 healthy subjects in conditions of a simulated central scotoma, blurred vision and oscillopsia. Texts were either blurred, set in motion or blanked at the gaze position by using eye tracking and gaze contingent display. The simulated visual impairment was calibrated such that all types of low vision caused equal reading impairment. We then tested the effect of magnification and contrast enhancement among the different types of low vision. We found that reading speed improved with increasing magnification and with higher contrast in all conditions. The effect of magnification was significantly different in the three low vision conditions: The gain from magnification was highest in simulated blur and least in central scotoma. Magnification eventually led to near normal reading speed in all conditions. High contrast was less effective than high magnification and the effect of contrast enhancement was similar in all low vision conditions. From these results we conclude that the type of low vision determines the benefit that can be expected from magnification. Contrast enhancement leads to similar improved reading speed in all low vision types. We provide evidence that supports the use of low vision aids.